Quality of life outcomes in children after surgery for Hirschsprung disease and anorectal malformations: a systematic review and meta-analysis. Issue 4 (10th November 2022) - Oltean, Irina; Hayawi, Lamia; Larocca, Victoria; Bijelić, Vid; Beveridge, Emily; Kaur, Manvinder; Grandpierre, Viviane; Kanyinda, Jane; Nasr, Ahmed
Abstract : Background: No systematic review and meta-analysis to date has examined multiple child and parent-reported social and physical quality of life (QoL) in pediatric populations affected by Hirschsprung's disease (HD) and anorectal malformations (ARM). The objective of this systematic review is to quantitatively summarize the parent-reported and child-reported psychosocial and physical functioning scores of such children. Methods: Records were sourced from the CENTRAL, EMBASE, and MEDLINE databases. Studies that reported child and parent reported QoL in children with HD and ARM, regardless of surgery intervention, versus children without HD and ARM, were included. The primary outcome was the psychosocial functioning scores, and the secondary outcomes were the presence of postoperative constipation, postoperative obstruction symptoms, fecal incontinence, and enterocolitis. A random effects meta-analysis was used. Results: Twenty-three studies were included in the systematic review, with 11 studies included in the meta-analysis. Totally, 1678 total pediatric patients with HD and ARM underwent surgery vs 392 healthy controls. Pooled parent-reported standardized mean (SM) scores showed better social functioning after surgery (SM 91.79, 95% CI (80.3 to 103.3), I 2 =0). The pooled standardized mean difference (SMD) showed evidence for parent-reported incontinence but not for constipation in children with HD and ARM after surgery that had a lower mean QoL score compared with the normal population (SMD −1.24 (-1.79 to –0.69), I 2 =76% and SMD −0.45, 95% CI (−1.12 to 0.21), I 2 =75%). The pooled prevalence of child-reported constipation was 22% (95% CI (16% to 28%), I 2 =0%). The pooled prevalence of parent-reported postoperative obstruction symptoms was 61% (95% CI (41% to 81%), I 2 =41%). Conclusion: The results demonstrate better social functioning after surgery, lower QoL scores for incontinence versus controls, and remaining constipation and postoperative obstruction symptoms after surgery in children with HD and ARM.